Gunpowder and Explosives, §§ 1-3, Article 18, The Code of the City of Annapolis (1897). - (:unkn) unknown (General Publisher, 1897)
No person or persons, shall keep in any store, vault, cellar, building or buildings, within the limits of said city, without special permission from the City Council, a greater quantity of gunpowder at any one time than fifty pounds, (which shall be secured in tin canisters or wooden kegs,) nor a greater quantity of dynamite or any other explosive not named, than five pounds, (which shall be well secured in tin canisters,) nor any nitro-glycerine whatever, under a penalty of not less than five nor more than twenty dollars for each offense; and every day such violation of this ordinance may continue or be persisted in shall constitute a separate and distinct offense.
--
Keywords: GUN POWDER STORAGE